A Preliminary Study of the Main Economic Effects of the Last Vat Reforms in the ue28, and in Particular in Spain - Vega Mocoroa, Isabel (Studia Oeconomica Posnaniensia, 2026)
The purpose of this article is to analyze the recent tax reforms regarding VAT in Europe and Spain and explain their main effects during the economic crisis, particularly with the recovery of government and the achievement of the Stability and Growth Pact and the effects on income redistribution. The need to increase revenue collection to reduce public deficit has forced the latest reforms of VAT in Europe, which led to, amongst other effects, an increase in implicit consumption tax rates, variation in the recovery ratio and a change in income distribution. The measures adopted by Spain, increasing VAT rates, broadening its base, and a reduction of categories subject to reduced rates and exemptions, have had unintended effects. Far from decreasing VAT fraud and decrease the GAP between the real and potential recovery, they have had very negative effects on consumption, resource allocation in certain sectors and, in general, income redistribution. It is important to consider that VAT is a regressive tax in nature. Since the achievement of some economic objectives might also cause negative impacts on others, we began to study the adverse effects on income distribution caused by the measures taken on VAT. In a future second step by means of an econometric model, developed on the Spanish family consumption survey, we try to evaluate the effects and draw conclusions on the various sectors affected and the reasons behind the chosen measures.